2014
DOI: 10.4149/neo_2014_011
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine clearance rate and serum creatinine concentration are related to delayed methotrexate elimination in children with lymphoblastic malignancies

Abstract: Methotrexate (MTX) is an effective treatment for childhood acute lymphoblastic leukemia (ALL) or Non-Hodgkin lymphoma (NHL); however, toxicity can arise with high doses MTX (HDMTX), especially in patients with delayed MTX elimination. Routine monitoring of plasma MTX concentrations is clinically important, but unfortunately is not always feasible. The aim of this study was to examine the relationship between MTX elimination and renal function to identify parameters that may be useful for predicting delayed MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…However, there have been controversial studies for relation between creatinine concentrations and plasma MTX levels. One study of children who received 3 or 5 g/m 2 of HDMTX has shown a positive correlation between serum creatinine concentrations and blood MTX levels whereas, another study for children who received 1 or 2 g/m 2 failed to show the positive association . Although creatinine clearance is not steady, it is unlikely that creatinine clearance may change during administration of HDMTX, since all patients were strictly monitored and maintained a high urine output and urinary alkalization during HDMTX administration in our study.…”
Section: Discussionmentioning
confidence: 53%
“…However, there have been controversial studies for relation between creatinine concentrations and plasma MTX levels. One study of children who received 3 or 5 g/m 2 of HDMTX has shown a positive correlation between serum creatinine concentrations and blood MTX levels whereas, another study for children who received 1 or 2 g/m 2 failed to show the positive association . Although creatinine clearance is not steady, it is unlikely that creatinine clearance may change during administration of HDMTX, since all patients were strictly monitored and maintained a high urine output and urinary alkalization during HDMTX administration in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, we investigated the hypothesis that evaluating renal function may be an appropriate means of monitoring plasma MTX concentrations after HDMTX for pediatric cancers. Additionally, previous studies reported the same findings regarding the correlation between Cr clearance and MTX concentration at the same time (7,23,24). On the contrary, other studies such as Joannon et al (25), Evans et al (26) and Relling et al (27) found that plasma MTX concentration was not correlated with Cr clearance.…”
Section: Discussionmentioning
confidence: 55%
“…One of the first surveys was based on creatinine level during and immediately after MTX infusions. They indicated the detrimental effect of methotrexate on renal function by lowering creatinine clearance and increasing serum creatinine, especially in patients with delayed MTX elimination [26][27][28]. In a group of 20 children with newly diagnosed ALL, treated with MTX at a dose of 5 g/m 2 , Ylinen et al observed an elevated cystatin C concentration 36 h after the infusion, but no changes in NGAL level were noted [29].…”
Section: Discussionmentioning
confidence: 99%